Torque Control of an In-Wheel Axial Flux Permanent Magnet Synchronous Motor using a Fuzzy Logic Controller for Electric Vehicles - Ha, Vo Thanh (Engineering, Technology & Applied Science Research, 2023)
This paper presents the control design of an in-wheel axial-flux permanent magnet synchronous motor with one stator and one rotor, using a fuzzy logic controller for electric vehicles. In this controller, the surgeon ambiguous inference file is built by two input vectors, the stator current error and the derivative of the stator error. These input variables include five membership functions: Negative Big (NB), Negative Small (NS), Equal Zero (ZE), Positive Small (PS), and Positive Big (PB). The fuzzy logic controller was implemented using a 5×5 matrix to meet the required output stator voltage of the controller. The fuzzy logic torque controller was compared with the PI controller in stator current response, torque, and speed. The proposed controller was evaluated using simulation results from MATLAB/SIMULINK.